Business Entity's Preventive-Anti-Crisis Strategy Model and Possibilities of Its Implementation in Georgia - Katamadze, Giorgi (Dr. Viktor Koval, 2022)
Introduction. In terms of modern hyperactive business processes, the stability and sustainable development of businesses are much at risk for managers and founders if they do not have an anti-crisis strategy; without an anti-crisis strategy, the business is sometimes completely destroyed by any unexpected negative event, or at best, has to deal with the consequences for a long time. Aim and tasks. The aim and objectives of the present paper are to determine the presence of anti-crisis mechanisms in the management methods of business companies operating in Georgia, the possibility of their implementation, the types of anti-crisis measures, the composition of the anti-crisis group, and the analysis of the skills of the group/members of anti-crisis management and their grouping/systematization/categorization. Results. The article presents the results of the research, based on the study of small and medium-sized business entities in Georgia, aiming at determining whether business entities use preventive-anti-crisis plans and strategies or not, how such strategies are formed, and in general, to what extent business entities are able to implement anti-crisis strategies. In the process of preparing the present research paper, both quantitative and qualitative methodologies were involved. In particular, cases were selected based on the following criteria: a) business entities which started and terminated their activities in the last 10 years; b) selection of business entities from different cities in Georgia; c) variety of business entities’ activities; statistical analysis; comparative method; component analysis; analysis of the official documentation. Conclusions. The types of strategies of economic entities in general have been studied and their general overview has been given. The stages and specific measures necessary for the development of individual preventive anti-crisis strategies for business entities, taking into account Georgian realities, are determined. The obtained results are analyzed and relevant recommendations are prepared on the basis of an integrated system approach.